Authoritical Parenting Patterns In The Moral Development Of Students In Islamic Religious Education Institutions - Sayyidah Syaehotin (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
The purpose of this study was to describe the authoritarian parenting pattern in the moral development of children in Islamic educational institutions. The research method in this study uses a qualitative approach. The research location is in Raudhatul Athfal Ar-Raihan Sukorejo, Bangsalsari, Jember. The technique of determining the informants used purposive sampling. Data collection techniques are observation, interviews, and documentation. Analysis of the data using the method proposed by Miles and Huberman, namely data condensation, data presentation, and drawing conclusions. The validity of the data using source triangulation and technical triangulation. The results showed that the moral development of children with parents who applied authoritarian parenting in guiding and nurturing their children developed well. Children with authoritarian parenting are able to achieve indicators of moral development in schools such as, children say greetings and salim, and children make mistakes in apologizing.